BTNL2 gene polymorphism and sarcoid uveitis. Issue 12 (14th March 2019) - Chaperon, Mayeul; Pacheco, Yves; Maucort-Boulch, Delphine; Iwaz, Jean; Perard, Laurent; Broussolle, Christiane; Jamilloux, Yvan; Burillon, Carole; Kodjikian, Laurent; Calender, Alain; Seve, Pascal
Abstract : Background: Uveitis is a frequent and early feature of sarcoidosis. As BTNL2 (butyrophilin-like 2) gene polymorphism was found linked with the susceptibility to sarcoidosis, we investigated whether a specific genotype of BTNL2 gene G16071A (or rs2076530) single-nucleotide polymorphism (SNP) would be associated with the risk of sarcoid uveitis in all patient subgroups. Methods: The study compared the genotype frequencies of SNP G16071A of 135 patients with sarcoid uveitis (Sa + Uv + ) with those of 196 patients with sarcoidosis without uveitis (Sa + Uv − ), 81 patients with uveitis without sarcoidosis (Sa − Uv + ), and 271 controls with no sarcoidosis nor uveitis (Sa − Uv − ). Three hypothetical subgroups of patients with sarcoid uveitis (Sa + Uv + cases) were considered: (1) subgroup I: patients aged <45 years of both sexes and all ethnic origins; (2) subgroup II: Caucasian women aged >45 years; and (3) subgroup III: all other patients. Results: A statistically significant difference in genotype frequencies was found between the groups Sa + Uv − and Sa − Uv − (p=3.2×10 −6 ) and between the groups Sa + Uv + and Sa + Uv − (p=7.1×10 −3 ). There was no difference between the three subgroups of Sa + Uv + patients. There was a statistically significant difference in genotype frequencies between Sa + Uv − and Sa + Uv + subgroup II (p=0.005) but no difference between Sa + Uv − and Sa + Uv + subgroup I. Conclusion: No association was found between G16071A and the susceptibility to sarcoid uveitis. BTNL2 gene G16071A SNP seems to be a predisposing factor for sarcoidosis except in Caucasian postmenopausal women with sarcoid uveitis in whom the GG genotype prevails. These and future results will help in understanding differences between particular subgroups of patients with sarcoid uveitis.